069 Prevalence of and Depression, Anxiety and Stress Associated with Premature Ejaculation among the Patients Attended in the Sex Clinic of a Tertiary Level Psychiatric Hospital, Dhaka, Bangladesh. (1st May 2022) - Nahar, S.; Shaheen, M.M.; Islam, T.; Alim, S.A.H. Mostafa; Alam, M.F.
ABSTRACT: Introduction: Premature Ejaculation (PE) has been considered as the most common male sexual dysfunction having significant detrimental impact on both men and their partners. But in many cases, it remains undetected and untreated. The relationship between depression, anxiety and stress with PE might be bi-directional. Depression, anxiety and stress may impair male sexual function and couple's sexual relationships. On the other hand, the poor sexual functioning and satisfaction can produce feelings of frustration and anxiety between partners. Objective: The objective of this study was to determine the proportion of PE and to find out the depression, anxiety and stress associated with PE among the men who perceive themselves as having little control over ejaculation attending in the sex clinic of a tertiary psychiatric hospital. Methods: This was a cross-sectional study conducted from August 2017 to June 2018, among 280 male patients who perceived themselves as having little control over ejaculation aged from 18 to 60 years and were selected by convenient sampling technique. A semi-structured, self-administered questionnaire containing socio-demographic variables, the Bangla version of the Premature Ejaculation Diagnostic Tool (PEDT), the Bangla version of the short version of Depression Anxiety Stress Scales (DASS 21-BV) were applied to assess their PE and associated depression, anxiety & stress respectively. Results: It showed that, mean (+ SD) age of the respondents was 38.8 (+8.44) years and 26.4% of the respondents were found to have premature ejaculation. Presence of PE was slightly higher (55.4%) among the older age group (aged 41-60 years) than the younger age group (aged 18-40 years). Chi-square test showed significant association with depression, anxiety and stress with PE (p<0.05 for all comparisons). Conclusions: This high prevalence and associated psychological factors illustrate the need for promoting awareness regarding PE and for better outcome. During assessment psychological factors should be identified properly and psychosocial management should be emphasized along with pharmacotherapy during management of the PE patients. Disclosure: Work supported by industry: no.